Production of bioelectricity for the aqueous extracts of some plants - Dyachok, Vasyl; Ivankiv, Oksana; Diachok, Iryna (Видавництво Львівської політехніки, 2024)
Annual climate conferences draw public attention to the urgent need to ecologize CO2-neutral fuel systems and recognize that global temperature increases must be limited to less than 2 °C to avoid dangerous climate change. Based on the projections of the International Panel on Climate Change, it is now widely accepted that in order to stay within this temperature range, CO2 emissions need to be reduced by 80 % by 2050. Furthermore, developing countries most affected by climate change are pushing for a reduction (as opposed to stabilization) of atmospheric CO2 equivalent levels from ~450 ppm to 350 ppm in order to stabilize at a 1.5 °C temperature rise. Electricity plays an important role in our everyday life, and its consumption is constantly increasing. Its traditional production based on fossil fuels has huge environmental problems, such as pollution of the atmosphere with greenhouse gases with further global consequences – the greenhouse effect. To overcome these effects, technologies based on non-conventional energy sources such as solar energy, wind energy, biofuels, etc. are being implemented. While solar photovoltaic and thermal energy are attractive, the need for bioenergy is becoming inevitable to replace fossil fuels. Natural photosynthesis offers the means for this, primarily through the use of plants. Land plants have already been used as a source of bioenergy, and this use will increase in the future, despite a number of associated problems. This study concerns a new technology of electricity production, namely, biotechnology, that is, the use of aqueous extracts of various plant resources. Some plants in nature have the ability to accumulate in their cells biologically active compounds capable of creating an electrolytic environment, in fact they are suitable for the production of electricity, which can be amplified.
Keywords: bioelectricity; vegetable raw materials; succulents; extract; biomass battery